MR Enterography in paediatric patients with obscure gastrointestinal bleeding. Issue 93 (August 2017) - Casciani, Emanuele; Nardo, Giovanni Di; Chin, Simone; Masselli, Gabriele; Polettini, Elisabetta; Oliva, Salvatore; Cozzi, Denis A; Cucchiara, Salvatore; Gualdi, Gianfranco
Highlights: Prospective study of MR enterography in evaluating obscure gastrointestinal bleeding (OGIB) in children. Good diagnostic yield (76%) in this application. Abstract: Objectives: To evaluate the performance of Magnetic Resonance enterography (MRE) in the diagnostic work-up of children presenting with obscure gastrointestinal bleeding (OGIB). Materials and methods: From January 2014 to January 2016, a single-centre prospective study was performed on all children between 0 and 16 years of age referred to the radiology department for OGIB. Each child underwent MRE examination after negative oesophagogastroduodenoscopy and ileocolonoscopy. MRE results were recorded. All patients proceeded to the related gold standard for diagnostic confirmation. Results: 25 patients (mean age 10.8 ± 4.5 years, range 4 months to 16 years) were included. MRE was diagnostic in 76% (19 of 25). The most frequent diagnoses were intestinal polyp (28%) and Meckel's diverticulum (16%). Sensitivity and specificity of MRE were 86% and 100% respectively. There were no reported complications during any of the examinations. Conclusion: MRE is a safe and accurate imaging modality in the evaluation of paediatric OGIB. Its diagnostic capability is comparable to current evidence for capsule endoscopy in this patient group. Further research with larger sample sizes and standardized control groups is warranted to improve our understanding of MRE in this application.